2002
DOI: 10.1023/a:1016393904439
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Our results show that burst suppression caused by the different anesthetics can be reliably detected with our segmentation and classification methods. The analysis of normal and pathological EEG, however, should include information of the anesthetic used. Knowledge of the normal variation of the EEG is necessary in order to detect the abnormal BSP of, for instance, seizure patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(34 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…No significant heterogeneity across the five recorded cortical sites was found. The frequency bandwidths in step (1) were varied: 5–30 Hz, 5–50 Hz, 3–125 Hz, 26 and the difference of <8 Hz and >47 Hz, 28 and found that 5–30 Hz and 5–50 Hz analyses yielded similar results, which were superior to the other two cases in almost all rats (in agreement with visual inspection). Furthermore, different values were tested for the threshold of mean+c*SD in step (3): c=3–7 and the one in best agreement with visual inspection was selected; c=3 for 8 and c=4 for 12 of 20 rats.…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…No significant heterogeneity across the five recorded cortical sites was found. The frequency bandwidths in step (1) were varied: 5–30 Hz, 5–50 Hz, 3–125 Hz, 26 and the difference of <8 Hz and >47 Hz, 28 and found that 5–30 Hz and 5–50 Hz analyses yielded similar results, which were superior to the other two cases in almost all rats (in agreement with visual inspection). Furthermore, different values were tested for the threshold of mean+c*SD in step (3): c=3–7 and the one in best agreement with visual inspection was selected; c=3 for 8 and c=4 for 12 of 20 rats.…”
Section: Methodssupporting
confidence: 63%
“…EEG epochs were analyzed from the beginning through the end of the 12.5 min duration of Acetylcholine (ACh) sample collection, to ensure parallel information for ACh sampling and EEG recording. To validate our results, we applied two alternative methods (variance-based method 27 and nonlinear energy operator-based method 28 ) to replace the amplitude approach in step (2). In the first alternative method, the standard deviation of the bandpassed signal was computed for each 200 ms interval with a 150 ms overlap; in the second method, the energy of the bandpassed signal was calculated by the nonlinear energy operator and smoothed using a 200 ms moving average.…”
Section: Methodsmentioning
confidence: 99%
“…It is characterised by alternating periods of normal to high voltage activity changing to low voltage. This kind of activity is usually seen when the concentration of anaesthetic drug is high [120,121]. To quantify this effect the burst suppression ratio (BSR) is calculated.…”
Section: Basic Design Characteristics Of Current Dga Monitorsmentioning
confidence: 99%
“…Previously, several methods have been proposed to detect the burst suppression pattern of EEG signals [34, 35]. However, we still need to overcome several drawbacks in the existing methods for constructing a practical burst suppression detection system in EEG recordings.…”
Section: Discussionmentioning
confidence: 99%